Mengeksplorasi Potensi Anak dalam Mengembangkan Bakat - Zahra Aulia Rachmadewi; Astuti Darmayanti (Quantum Wellness : Jurnal Ilmu Kesehatan, 2024)
Education is basically the process of developing one's talents and interests internally. Every child must have advantages and disadvantages, and talent is a term commonly used to describe the advantages that someone possesses. Every talent a child possesses must be developed so that their abilities can benefit in the future. A person's talent and interests are cultivated to educational goals because talent is a potential that requires serious and systematic development and training to realize. There are two factors that support the development of talent and interests: internal factors and external factors. The ways to identify interests and talents are as follows: recognize yourself, know what you want, value yourself, find talent, and combine interest and utility. There might be other ways. Ways to cultivate talent and interest: You need courage, get support from practice, get the support of the environment, and understand the challenges and how to deal with them. There needs to be an increase in knowledge about the definition of talent and interests, the substantive dimensions of talent, interest, methods of identifying a person's talent, and methods for developing talent